Current insights in the complexities underlying drug-induced cholestasis. (3rd July 2019) - Deferm, Neel; De Vocht, Tom; Qi, Bing; Van Brantegem, Pieter; Gijbels, Eva; Vinken, Mathieu; de Witte, Peter; Bouillon, Thomas; Annaert, Pieter
Abstract: Drug-induced cholestasis (DIC) poses a major challenge to the pharmaceutical industry and regulatory agencies. It causes both drug attrition and post-approval withdrawal of drugs. DIC represents itself as an impaired secretion and flow of bile, leading to the pathological hepatic and/or systemic accumulation of bile acids (BAs) and their conjugate bile salts. Due to the high number of mechanisms underlying DIC, predicting a compound's cholestatic potential during early stages of drug development remains elusive. A profound understanding of the different molecular mechanisms of DIC is, therefore, of utmost importance. Although many knowledge gaps and caveats still exist, it is generally accepted that alterations of certain hepatobiliary membrane transporters and changes in hepatocellular morphology may cause DIC. Consequently, liver models, which represent most of these mechanisms, are valuable tools to predict human DIC. Some of these models, such as membrane-based in vitro models, are exceptionally well-suited to investigate specific mechanisms ( i.e. transporter inhibition) of DIC, while others, such as liver slices, encompass all relevant biological processes and, therefore, offer a better representation of the in vivo situation. In the current review, we highlight the principal molecular mechanisms associated with DIC and offer an overview and critical appraisal of the different liver models that are currently being used to predict the cholestatic potential of drugs.